Resonant energy transfer enhances solar thermal desalination. Issue 3 (19th February 2020) - Alabastri, Alessandro; Dongare, Pratiksha D.; Neumann, Oara; Metz, Jordin; Adebiyi, Ifeoluwa; Nordlander, Peter; Halas, Naomi J.
Abstract : Water production from solar thermal desalination is limited by the energy consumption of phase change. Resonant heat exchange between matched saline feed and purified distillate flow rates enables optimized recovery of vaporization energy. Abstract : Evaporation-based solar thermal distillation is a promising approach for purifying high-salinity water, but the liquid-vapor phase transition inherent to this process makes it intrinsically energy intensive. Here we show that the exchange of heat between the distilled and input water can fulfill a resonance condition, resulting in dramatic increases in fresh water production. Large gains (500%) in distilled water are accomplished by coupling nanophotonics-enabled solar membrane distillation with dynamic thermal recovery, achieved by controlling input flow rates as a function of incident light intensity. The resonance condition, achieved for the circulating heat flux between the distillate and feed, allows the system to behave in an entirely new way, as a desalination oscillator. The resonant oscillator concept introduced here is universal and can be applied to other systems such as thermal energy storage or solar-powered chemical reactors.